Sickness and Treatment: A Situation Analysis among the Garments Workers - Rahman, Md Atiqur; Rahman, Md Mahfuzar (Anwer Khan Modern Medical College Journal, 2013)
This was a descriptive type of cross sectional study among 522 garments workers as respondents. It was aimed to identify morbidity pattern, duration of illness among garments workers and also to determine treatment seeking behavior during illness. The socio-demographic characteristics of the respondents were the points of investigations. It was revealed from the findings that the mean age of the respondents were 23.1years. They were mostly female (80%) and married (60%). About 60% respondents were found primarily educated and no one found illiterate. 90% respondents were found from nucleated family. The study shows 79% respondents were suffering from illness during the last 02 months and majority suffers (18.6%) and (43.6%) were found among 26-30 years age groups and 21-25 years age groups respectively. However, female sufferers were more (33.6%) than male (10%) in the 21- 25 years age groups. Moreover about 42% respondents were suffering for 1-2 weeks and 28.8 are suffering for less than 02 weeks. On the otherhands, Loose motion, Cough, and Breathlessness were found prominent sign/symptoms among 38%, 29%, 28% sufferers respectively. Diarrhoea, Common cold and Respiratory Tract Infections were found as predominant diagnosis among 40.5%, 22.5% & 15.1% respondents respectively. Nevertheless majority 56% were seeking treatment from LMAF doctors. Conclusion: The study findings highlight awareness program among factory owners and garments workers towards preventing infectious and chronic diseases as well as to undertake modern scientific treatment. Improved health care facilities in the garments factory may be considered for early detection and treatment of cases to avoid complications. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13678 AKMMC J 2013: 4(1): 10-14